EL SACELLUM DEDICADO A IUPPITER STATOR EN CARTAGENA - Amante Sánchez, Manuel; Martín Camino, Miguel; Pérez Bonet, Mª Ángeles; González Fernández, Rafael; Martínez Villa, Mª Ángeles (Antigüedad y Cristianismo, 1995)
At the foot of a small flat elevation in Cabezo Gallufo, Cartagena, Murcia, the remains of a small cut building was found and rapidly excavated. In one of the pavements an inscription was discovered made up of white tesellae measuring 0.01 X 0.1 m. It rads as follows: M. AQVINI. M L. ANDRO / IOVI. STATORI. DE SVA P QVR 1 L. M